2021
DOI: 10.1021/acsami.1c02540
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional/Bidirectional Electron Transfer at the Au/TiO2 Interface Operando Tracked by SERS Spectra from Au and TiO2

Abstract: Although it is well-known that the size can influence the surface plasmon resonance property of coinage metals and the electronic state of the Mott–Schottky junction formed at the metal/semiconductor interface, insights into how the size can be exploited to optimize the photocatalytic activity and selectivity of metal/semiconductor composites are lacking. Here we utilize operando SERS spectroscopy to identify the size effect on the electron-transfer dynamics and the direction at the Au/TiO2 interface. This eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The enhancement in the photocurrent density is produced by the synergetic co-sensitizing effect of CNQDs and AuNPs. It is well-established that hot electrons produced by Landau damping of the surface plasmon in AuNPs can be efficiently injected into the conduction band of crystalline TiO 2 at timescales of roughly 50–250 ps. These photogenerated electrons are extracted by the TNRs, which present vertical percolation pathways for the electrons to reach the FTO substrate and finally the cathode. Recent work has shown that hot holes produced by interband damping in AuNPs can tunnel through thin TiO 2 layers to efficiently oxidize OH – ions in the KOH electrolyte.…”
Section: Pec Measurementsmentioning
confidence: 99%
“…The enhancement in the photocurrent density is produced by the synergetic co-sensitizing effect of CNQDs and AuNPs. It is well-established that hot electrons produced by Landau damping of the surface plasmon in AuNPs can be efficiently injected into the conduction band of crystalline TiO 2 at timescales of roughly 50–250 ps. These photogenerated electrons are extracted by the TNRs, which present vertical percolation pathways for the electrons to reach the FTO substrate and finally the cathode. Recent work has shown that hot holes produced by interband damping in AuNPs can tunnel through thin TiO 2 layers to efficiently oxidize OH – ions in the KOH electrolyte.…”
Section: Pec Measurementsmentioning
confidence: 99%
“…Thus, the charge transfer between TiO 2 and Ag could cause the enhancement of the localized surface plasmon resonance (LSPR) and favor the measurement of adsorbed molecules on the Ag domains, leading to an increase of the SERS activity. [36][37][38][39] Meanwhile, the Ag NPs are conducive to the effective separation of photogenerated electrons and holes, which can improve the photocatalytic activity of the TiO 2 .…”
Section: Sers Spectra and Sensitivitymentioning
confidence: 99%
“…A typical example is the construction of a plasmonic metal/semiconductor heterojunction to promote the Raman scattering or photocatalytic efficiency of the molecules adsorbed on plasmonic metals. 21,23,26 Although improved performance has been well presented, most of these studies did not accurately discuss the physical origins behind it or simply assume that the charge flows from the semiconductor to the plasmonic metal and then to the molecules, which seems to be plausible but insufficient.…”
mentioning
confidence: 99%
“…The heterojunction composed of plasmonic metals and semiconductors provides a unique paradigm for concentrating and manipulating incident light. It sets off multiple interfacial charge transfer processes in the heterojunction to enhance light absorption, generate plasmonic hot carriers, and facilitate the light–matter interactions. These charge transfer processes may arise from light-induced direct charge transfer, , plasmon-assisted hot carrier transfer, and charge redistribution between the plasmonic metal and semiconductor and have been extensively applied to increase the photoelectric conversion efficiency in photovoltaics, , boost the photocatalytic reactions, and strengthen the photoluminescence and Raman scattering for sensing applications. …”
mentioning
confidence: 99%
See 1 more Smart Citation